Radiation Synthesis of Methacrylic Acid/Poly (2-Ethyl-2-Oxazoline) Copolymer Hydrogel for Colon-Specific Drug Targeting Delivery System (Journal of Nuclear Technology in Applied Science, 2019)
PH-sensitive hydrogels composed of Methacrylic acid and Poly (2-ethyl-2-oxazoline) (MAAc/PEOz) were prepared by means of γ-radiation induced graft copolymerization and crosslinking. The preparation parameters such as feed solution composition and concentration and irradiation dose were optimized. The effect of pH on the equilibrium of swelling for the prepared hydrogels was examined. Studying the diffusion’s parameters and coefficient as a function of the pH values for the surrounding solution showed obvious changes in the swelling parameters as a result of changing the surrounding solution pH values. In order to estimate the ability of the prepared copolymer to be used as a colon-specific drug carrier, the release of indomethacin was monitored as a function of time at pH 3 and pH 7. The observed results show the capability of the prepared hydrogel to protect the contained model drug at buffer solution of pH 1 and start releasing the drug as soon as the hydrogel transferred to buffer solution of pH 7. Such data would recommend the prepared hydrogel as a promising candidate for colon specific drug delivery system.
Keywords: Copolymerization; Gamma-Radiation; Swelling Kinetics; Drug Delivery System